CHALLENGES IN DEVELOPING ANNUAL AND SUSTAINABILITY REPORTS: IS DATA MANAGEMENT MATTER? - Angelica Valerie Amaranydia; Aghnia Nadhira Aliya Putri (International Journal of Contemporary Accounting, 2023)
This study examines the multifaceted approval process in the preparation of Company X's annual and sustainability report, a subsidiary of a State-Owned Enterprise (SOE). The report's crafting involves various stages, from initial data collection fraught with reliability issues to final consensus-driven approval before release. The process is marked by intense scrutiny and a necessity for alignment with the company's strategic vision and the rigorous standards set by its leadership. Despite the application of best practices and lessons from previous research, the team encountered significant challenges, such as data inconsistency, excessive irrelevant information, and a lack of coordination between different reporting segments. These issues necessitated iterative revisions, meticulous translation accuracy, and careful management of stakeholder feedback. The study delineates the complexities of each phase of report preparation, highlighting the critical importance of the approval phase as a crucial gateway that ensures the report's quality, accuracy, and resonance with the company's strategic and brand considerations.